2022
DOI: 10.1084/jem.20221350
|View full text |Cite
|
Sign up to set email alerts
|

Distinct fibroblast progenitor subpopulation expedites regenerative mucosal healing by immunomodulation

Abstract: Injuries that heal by fibrosis can compromise organ function and increase patient morbidity. The oral mucosal barrier has a high regenerative capacity with minimal scarring, but the cellular mechanisms remain elusive. Here, we identify distinct postnatal paired-related homeobox-1+ (Prx1+) cells as a critical fibroblast subpopulation that expedites mucosal healing by facilitating early immune response. Using transplantation and genetic ablation model in mice, we show that oral mucosa enriched with Prx1+ cells h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…(a-j) N = 5-7 per group for a total of 12 mice. Student's t-test, *p < 0.05, **p < 0.01, ***p < 0.001.facilitates a quicker transition to resolution of inflammation (Iglesias-Bartolome et al, 2018;Ko et al, 2023). In this study, we found that the expression of CXCL1 and CCL2 was substantially elevated in Prx1Cre + fibroblasts.…”
supporting
confidence: 50%
See 3 more Smart Citations
“…(a-j) N = 5-7 per group for a total of 12 mice. Student's t-test, *p < 0.05, **p < 0.01, ***p < 0.001.facilitates a quicker transition to resolution of inflammation (Iglesias-Bartolome et al, 2018;Ko et al, 2023). In this study, we found that the expression of CXCL1 and CCL2 was substantially elevated in Prx1Cre + fibroblasts.…”
supporting
confidence: 50%
“…We examined day 4 wounds, an early time point during which the inflammatory phase is still active (Ko et al., 2023). The immunofluorescence experiment on day 4 oral wound was performed to quantify nuclear NF‐κB expression, indicative of its translocation and activation, in spindle‐shaped vimentin + fibroblasts which were either immunopositive for Prx1 + or not (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, Ko et al (2022) delve into the mechanisms underlying oral regeneration by comparing injury responses in the anterior region of the palate (rugae 2, or R2), which heals rapidly, to posterior palate (R4) wounds that are slow to heal (see figure). In doing so, they identify a unique paired-related homeobox-1 + (Prx1 + ) fibroblast progenitor population in the R2 palate that is missing from the R4 palate.…”
mentioning
confidence: 99%